(untitled) (Asian Journal of Medical and Biological Research, 2017)
Individual selection is particularly indispensable in selection experiments for body weight in quail. Body weight is highly heritable trait. The study was conducted with the objective to assess the productive and reproductive performance and expected response to selection of second generation (G2) of four quail varieties conserved at Bangladesh livestock Research Institute. At 5th week of age, quails of first generation (G1) were selected on the basis of breeding value according to their 5th week body weight. A total of 1953-day-old chicks were hatched in two batches for producing second generation (G2). Diet containing 24% crude protein and 3000 kcal ME/kg were provided to the birds. The data were analyzed in a CRD factorial arrangement by General Linear Model (GLM) Univariate Procedure in SPSS Computer Program. The highest fertility was observed in White (98.31%) variety and hatchability was in Japanese (97.75%) variety. Differences in chick weight at hatch between White and Brown, Brown and Japanese, Japanese and Black, Black and White were approximately 6.90%, 2.74%, 6.20% and 10.51% respectively. The effect of variety and batch on 5th week body weight was significant (p<0.001) but interaction effect of variety and batch was not significant (p>0.05). Black quail had significantly (?2 = 25.00; p<0.01) higher (17.62%) chick mortality than that of other three varieties. As a result of selection, body weight at 5th weeks of age was expected to improve by 4.34g vs. 6.51g; 1.21g vs. 4.33g, 1.68g vs. 3.77g and 1.02g vs. 2.40g respectively for Japanese, White, Brown and Black males and females quail genotypes. It is therefore can be concluded that the White variety is superior in terms of higher body weight and higher fertility and medium chick mortality among the four quail varieties. In each generation, slight response was obtained for selection. Asian J. Med. Biol. Res. December 2016, 2(4): 631-634